Rekontruksi Penjatuhan Pidana Uang Pengganti Tindak Pidana Korupsi Perspektif Ratio Decidendi: Studi Kasus Putusan Nomor 135/PID.SUS-TPK/2022/PN SMG - FAHMY ASYHARI (CV Rewang Rencang, 2023)
The imposition of substitute money sentences in corruption crimes is often found to differ from each defendant in the same corruption crime. This condition reflects a sense of injustice for the state, perpetrators and society/victims. This paper aims to determine the application of substitute money sentences in the practice of organizing criminal justice in Decision Number 135/Pid.Sus-TPK/2022/PN Smg and the reconstruction of substitute money sentences in corruption crimes using the ratio decidendi perspective. The results of the study show that First, the application of substitute money sentences in Decision Number 135/Pid.Sus-TPK/2022/PN Smg on behalf of Sapto Sri Winarno has different decisions from other defendants in the same case so that it has a direct impact on the return of state losses in the form of the realization of substitute money not running optimally so that legal uncertainty and does not create a deterrent effect for future corruption convicts. Second, the reconstruction of substitute money sentences in corruption crimes should be that judges in deciding to impose substitute money sentences should use the ratio decidendi perspective even though the prosecutor's demands do not include substitute money sentences.